Seeding times of irrated rice cultivars - Soares, Sammy Fernandes; Filho, Domingos Fornasieri; Salgado, José Sérgio (Pesquisa Agropecuaria Brasileira, 1995)
Aiming at a better land utilization in the meadow soils of Cachoeiro de Itapernirim, Espírito Santo, Brazil, through the obtention of more than one irrigated rice (Oryza sativa L.) harvest per year in the same area, the behaviour of two cultivars, (CICA 8 and BR-IRGA 410) planted every month was evaluated, during the years 1987/88 and 1988/89. The experimental design used was randomized blocks with six and four replications in first and second year, respectively. Highest yields were obtained for 'CICA 8' with seedings performed firom July to October, and for 'BR-IRGA 410' with plantings from August to February in the first year, and for both cultivars with seedings from August to January in the second year. The results obtained allow to specify that two irrigated rice harvests per year can be obtained in the same area, and, the best seeding times for such a purpose are in August and January.